Plasma Cell Gingivitis: A Case Report - N Lamdari; S Pradhan (Journal of Nepal Medical Association, 2012)
Plasma cell gingivitis is a rare benign condition of the gingiva of unknown etiology characterized by sharply demarcated erythematous and edematous gingiva often extending to the mucogingival junction. This is sometimes considered as a hypersensitive reaction. It presents clinically as a diffuse, erythematous and papillary lesion of the gingiva, which frequently bleeds with minimal trauma. The histological appearance consists of a dense infiltration of normal plasma cells separated by collagenous stroma, usually confined to free and attached gingiva. The lesion can be eliminated by identifying and avoiding the source of the allergen along with nonsurgical periodontal therapy. We report a 29-years-old female patient diagnosed clinically as plasma cell gingivitis and confirmed histologically. The patient gave history of herbal dentifrice for a period of one year. Nonsurgical periodontal therapies along with discontinuation of herbal dentifrice lead to remission of the condition within a month.